FAKTOR-FAKTOR YANG MEMPENGARUHI PETANI KOPI DI DESA PULOSARI KECAMATAN PANGALENGAN DALAM MEMILIH SISTEM POLA TANAM MONOKULTUR DAN POLIKULTUR - Elza Rosalia; Tuti Karyani (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Coffee commodity is very potential and has markets both domestically and abroad. Bandung Regency is one of the coffee producers who strives to develop the quality and quantity of coffee in order to improve the welfare of the community. To meet the market demand, farmers have different ways, especially in the application of planting patterns, where currently there are growing coffee monoculture and polyculture. The research objective is to identify monoculture and polyculture farmers' income and analyze the factors that influence coffee farmers to choose a monoculture and polyculture cropping system. Data analysis using logistic regression methods. The results showed monoculture farmers' income was higher than polyculture income without adding up income from vegetables. However, the income of monoculture farmers is lower than the income of polyculture by adding income from vegetables. The logistic regression test results show that the factors that influence farmers to choose a planting pattern are the age of the farmer, the distance of the farm to the farmer's residence, the distance of the farm to the coffee processing plant, and the age of the coffee plant.